2015
DOI: 10.4236/jemaa.2015.73008
|View full text |Cite
|
Sign up to set email alerts
|

Radiated Ultrashort High-Power Electromagnetic Pulses Induce ATP Release in B16F10 Murine Melanoma Cells

Abstract: Ultrawideband electromagnetic pulses with high amplitude and short duration are reported to affect several aspects of cell physiology. They are usually delivered to the living material through electrodes in small dedicated chambers. Here we showed, using a totally different experimental setup, that radiated EM pulses illuminating the living material through a specialized antenna (without any direct contact) are able to trigger a rapid release of ATP in cultured murine cells that was concomitant with a drop of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…6a and b, 180 min), suggesting that the ascorbic acid‐glutathione cycle (and thus ROS homeostasis) was affected by exposure to nsEMP. The energy state of the cell appeared to be widely affected after both high frequency (900 MHz) continuous wave in plants [Roux et al, 2008] or ns‐EMP in animal cells [Macaire et al, 2015] where ATP level was rapidly (30 min) and consistently decreased after exposure, potentially triggering AMPK signaling pathway [Morotomi‐Yano et al, 2012]. Here we monitored the expression level of the plant energy sensor SnRK1, known to rapidly increase in case of energetic crisis (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6a and b, 180 min), suggesting that the ascorbic acid‐glutathione cycle (and thus ROS homeostasis) was affected by exposure to nsEMP. The energy state of the cell appeared to be widely affected after both high frequency (900 MHz) continuous wave in plants [Roux et al, 2008] or ns‐EMP in animal cells [Macaire et al, 2015] where ATP level was rapidly (30 min) and consistently decreased after exposure, potentially triggering AMPK signaling pathway [Morotomi‐Yano et al, 2012]. Here we monitored the expression level of the plant energy sensor SnRK1, known to rapidly increase in case of energetic crisis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those of Cavagnaro et al (2013) suggesting that the signal attenuation of ultrawideband pulses in human tissues was significantly induced with frequency, being of about 100 dB near 3 GHz. While being of much smaller amplitude and using emitted EMPs rather than electric field generated by immersed electrodes, the set‐up used in this study (30,000 EMP of 500 ps, 237 kV m −1 ) was previously shown to induce cellular changes in cultured MMLV murine cells with a reduction of adenosine triphosphate (ATP) content [Macaire et al, 2015]. The observation of Beebe et al [2012] showing that short EMP (15 ns) affect mitochondria suggested that this could be due to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%